(untitled) (World Bulletin of Social Sciences, 2025)
This article distinguishes the socio-psychological competencies aimed at enhancing the effectiveness of creative-innovative education characteristic of the professional activity of teachers. Through their analysis, the scientific views of scholars regarding the possibility of identifying many essential characterological qualities important for both students and teachers are examined.